Alternative splicing of bunched confers a dual role in hippo pathway-dependent growth and tumorigenesis. - Guo, P.; Song, S.; Niu, Y.; Kuang, X.; Zhou, D.; Zhou, Z.; Zhang, Y.; Ma, X. (Oncogene, 2025)
Alternative splicing is a fundamental mechanism that generates functionally distinct proteins from individual genes, contributing to gene regulation and proteomic diversity. In Drosophila, the bunched (bun) gene, a member of the TSC-22 domain gene family, undergoes alternative splicing, yielding diverse protein isoforms involved in crucial biological processes. Nevertheless, the specific roles and regulatory mechanisms of each isoform remain elusive. Here, we employed CRISPR/Cas9 technology to introduce targeted deletions within the endogenous locus of the bun gene, resulting in the removal of either long or short isoforms. We discovered that the short isoforms demonstrated a growth-suppressive role, whereas the long isoforms exhibited a growth-promoting effect. Surprisingly, the long isoforms exhibited a remarkable dual functionality, as both deletion and amplification of long isoform expression impede the excess growth induced by Hippo pathway inactivation. Mechanistically, ectopically expressed Bun long isoforms act as the transcriptional suppressor by competitively binding to targets' promoter regions in conjunction with Yorkie/Scalloped (Yki/Sd), thereby inhibiting its transcriptional outputs and ultimately leading to the growth suppression. These findings unveil the intricate interaction between distinct spliced isoforms of Bun and oncogenic outcomes, highlighting Bun long isoforms as the critical transcription suppressor regulating Hippo pathway inactivation-mediated growth and tumorigenesis in Drosophila.